Ulcerative Colitis and Neopterin: Related? - Beşir Kesici (Boğaziçi Tıp Dergisi, 2019)
INTRODUCTION[|]Ulcerative colitis (UC) is a chronic inflammatory bowel disease that invades the colon mucosa and progresses with remissions and exacerbations. Neopterin is a biochemical marker of cell-mediated immunity. Studies have demonstrated increased levels of neopterin in inflammatory bowel diseases. The aim of this study was to examine the relationship between the Truelove-Witts criteria and the level of neopterin in UC patients, as well as the usefulness of neopterin in determining the activity of the disease.[¤]METHODS[|]Thirty-three patients who were followed-up for UC in the gastroenterology clinic of a single hospital were enrolled in the study and divided into 3 groups: mild, moderate, and severe UC, according to the Truelove-Witts activity index. A control group of 43 healthy individuals was also included in the study. The neopterin level of the patient and the control groups was examined and the relationship was statistically analyzed.[¤]RESULTS[|]No statistically significant difference was detected in the median neopterin level between the patient and the control groups.[¤]DISCUSSION AND CONCLUSION[|]These results demonstrated that the serum neopterin level remained unchanged in patients with UC when compared with the control group, and that age and gender did not have any specific impact on this outcome.[¤]